2011
DOI: 10.3802/jgo.2011.22.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome of women with synchronous cancers of endometrium and ovary: a 10 year retrospective cohort study

Abstract: ObjectiveSynchronous occurrence of endometrial and ovarian tumors is uncommon, and they affect less than 10% of women with endometrial or ovarian cancers. The aim of this study is to describe the epidemiological and clinical factors; and survival outcomes of women with these cancers.MethodsThis is a retrospective cohort study in a large tertiary institution in Singapore. The sample consists of women with endometrial and epithelial ovarian cancers followed up over a period of 10 years from 2000 to 2009. The epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 15 publications
6
48
0
Order By: Relevance
“…21,22 However, with synchronous primary endometrial and ovarian cancers, the correlation with endometriosis is still controversial because the occurrence of ovarian cancer ranges from 30% to 90%. 2,17,19 Our data strengthen the role of endometriosis as being involved in the pathogenesis for synchronous primary endometrial and ovarian cancers. In addition, our data suggest a relationship between infertility history and the development of synchronous primary endometrial and ovarian cancers because there were 9 patients with a history of infertility, and 6 of these patients had endometriosis.…”
Section: Discussionsupporting
confidence: 74%
“…21,22 However, with synchronous primary endometrial and ovarian cancers, the correlation with endometriosis is still controversial because the occurrence of ovarian cancer ranges from 30% to 90%. 2,17,19 Our data strengthen the role of endometriosis as being involved in the pathogenesis for synchronous primary endometrial and ovarian cancers. In addition, our data suggest a relationship between infertility history and the development of synchronous primary endometrial and ovarian cancers because there were 9 patients with a history of infertility, and 6 of these patients had endometriosis.…”
Section: Discussionsupporting
confidence: 74%
“…Zaino R et al reported 86% 5 year survival and 80% 10 year survival [3] . Another report has shown a mean survival of 84% 6 . Yuantaoliu et al reported a mean survival of 109 months and rate of 93.5% in stage I and stageIItumours [7] .Presentation at an early stage may be attributed to the overall good prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Y Chiang et al done on 23 cases of synchronous ovarian and endometrial tumours 63% showed similar histology [5] . A 10 year study done by Young Kuei Lim et al on 75 patients with synchronous tumours showed 73.9% being endometrioid endometrial cancers and 26.1 % with tumours of different histological type [6] . Yuantaoliu et al reported 43 cases of synchronous tumours of which 30% showed dissimilar histology [7] .There are only a few reports of synchronous endometrial carcinoma with an ovarian carcinoma of mucinous morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for familial history used in the study should be clearly specified. Therefore, definitive incidence of HNPCC using clinical criteria could be clearly depicted.The proportion of both endometrioid adenocarcinoma in endometrium and ovary were 50% (18/36) and 74% (34/46) from Korea and Singapore, respectively [3,4]. The authors from two studies could reveal the proportion of synchronous tumor from metachronous tumor among both endometriod histology in endometrium and ovary from cancer registry of endometrial cancer and ovarian cancer, respectively.…”
mentioning
confidence: 95%
“…The proportion of genetic background and germline mutation in Korean women with gynecologic cancer is comparable to those of western ethnics [1,2]. Two interesting articles dealing synchronous cancers of endometrium and ovary appeared in the December issue [3,4]. The 5-year overall survival of women with synchronous cancers of endometrium and ovary was 78% from Singapore [3].…”
mentioning
confidence: 96%